A Comparative Clinical Study to Evaluate the Effect of Sigru Leaf Powder and Sigru Bark Powder in the Management of Sannipatika Pandu with Reference to Sickle Cell Anemia - Bez, Sudipta; Nayak, Utkalini; Panda, Pradip Kumar; Sahu, Manoranjan; Dutta, Amrit (International Research Journal of Ayurveda & Yoga, 2024)
Background: Various ailments are related to Panduroga, either as a symptom or as an Upadrava, according to Ayurvedic literature. The present clinical study is a humble effort to assess the effect of the trial drug, Sigru leaves powder and Sigru bark powder on Sannipatika Pandu (sickle cell anemia). Materials and Methods: A total of 30 patients of Sannipatika Pandu (sickle cell anemia) were taken for the present study, 15 patients each in Group A (Trial Group-1) and Group B (Trial Group-2). This is a clinicopathological study (single-blind study). Group A (Trial Group-1): 15 patients were treated with Sigru leaves powder 3 g twice daily with water for 30 days after food. Group B (Trial Group-2): 15 patients were treated with Sigru bark powder 3 g twice daily with water for 30 days after food. Results and Discussion: As per the statistical tests, we can conclude that there is no significant change observed in Group A and Group B. Conclusion: It is found that the trial medications can be safely supplied to everyone for an extended period of time and may offer the best chance of recovery for sickle cell anemia.